Effect of a policy to reduce user fees on the rate of skilled birth attendance across socioeconomic strata in Burkina Faso. Issue 4 (8th October 2015) - Langlois, Étienne V; Karp, Igor; Serme, Jean De Dieu; Bicaba, Abel
Abstract : Background. In Sub-Saharan Africa, maternal and neonatal morbidity and mortality rates are associated with underutilization of skilled birth attendance (SBA). In 2007, Burkina Faso introduced a subsidy scheme for SBA fees. The objective of this study was to evaluate the effect of Burkina Faso's subsidy policy on SBA rate across socioeconomic status (SES) strata. Methods. We used a quasi-experimental design. The data sources were two representative surveys ( n  = 1408 and n  = 1403) of women from Houndé and Ziniaré health districts of Burkina Faso, and a survey of health centres assessing structural quality of care. Multilevel Poisson regression models were used with robust variance estimators. We estimated adjusted rate ratios (RR) and rate differences (RD) as a function of time and SES. Results. For lowest-SES women, immediately upon the introduction of the subsidy policy, the rate of SBA was 45% higher (RR   = 1.45, 95% confidence interval (CI): 1.19–1.77) than expected in the absence of subsidy introduction. The results indicated a sustained effect after introduction of the subsidy policy, based on RR estimate (95% CI) of 1.48 (1.21–1.81) at 2 years. For middle-SES women, the RR estimates were 1.28 (1.09–1.49) immediately after introduction of the subsidy policy and 1.30 (1.11–1.51) at 2 years, respectively. For highest-SES women, the RR estimates were 1.19 (1.02–1.38) immediately after subsidy introduction and 1.21 (1.06–1.38) at 2 years, respectively. The RD (95% CI) was 14% (3–24%) for lowest-SES women immediately after introduction of the policy, and the effect was sustained at 14% (4–25%) at 2 years. Conclusion. Our study suggests that the introduction of a user-fee subsidy in Burkina Faso resulted in increased rates of SBA across all SES strata. The increase was sustained over time and strongest among the poorest women. These findings have important implications for evidence-informed policymaking in Burkina Faso and other countries in Sub-Saharan Africa.